Characterisation of divertor detachment onset in JET-ILW hydrogen, deuterium, tritium and deuterium–tritium low-confinement mode plasmas. (March 2023) - Groth, M.; Solokha, V.; Aleiferis, S.; Brezinsek, S.; Brix, M.; Carvalho, I.S.; Carvalho, P.; Corrigan, G.; Harting, D.; Horsten, N.; Jepu, I.; Karhunen, J.; et al.
Highlights: This paper presents characterisation of the plasma conditions in the low-field side divertor in JET ITER-like Wall hydrogen, deuterium, tritium and deuterium–tritium plasmas showing that: The core plasma density required to detach the LFS divertor plasma is independent of the hydrogenic species protium, deuterium and tritium, and a 40%/60% deuterium–tritium mixture. The detachment onset density is independent of the operational status of the JET cryogenic pump. The onset of detachment coincides with electron temperatures in the low-field side divertor plasma between 2 eV and 3 eV. The electron density peaks in the low-field side divertor at core density when the electron temperature at the low-field side divertor plate is 1 eV, which is higher than the divertor detachment onset density. The density limit was found approximately 20% higher in protium than in tritium and deuterium–tritium plasmas. Abstract: Measurements of the ion currents to and plasma conditions at the low-field side (LFS) divertor target plate in low-confinement mode plasmas in the JET ITER-like wall materials configuration show that the core plasma density required to detach the LFS divertor plasma is independent of the hydrogenic species protium, deuterium and tritium, and a 40 %/60 % deuterium–tritium mixture. This observation applies to a divertor plasma configuration with the LFS strike line connected to the horizontal part of the LFS divertor chosen because of its superior diagnostic coverage. The finding is independent of the operational status of the JET cryogenic pump. The electron temperature (Te ) at the LFS strike line was markedly reduced from 25 eV to 5 eV over a narrow range of increasing core plasma density, and observed to be between 2 eV and 3 eV at the onset of detachment. The electron density (ne ) peaks across the LFS plasma when Te at the target plate is 1 eV, and spatially moves to the X-point for higher core densities. The density limit was found approximately 20 % higher in protium than in tritium and deuterium–tritium plasmas.